Macroeconomic Policy Reforms and Economic Performance in Malawi 1960-2013 - Chirwa, Themba Gilbert; Odhiambo, Nicholas M. (Iberoamerican Journal of Development Studies, 2015)
The paper discusses the role that government policies and macroeconomic reforms have played in influencing economic growth in Malawi during the period 1960-2013. The study identifies a Stateregulated economic system that dominated the Malawian economy, in which economic growth patterns were influenced mainly by activities financed by the State. Two fundamental challenges are identified that have led to a subdued performance of the economy – the crowding-out effect of State-interventionism affecting private sector-led growth; and regulatory arbitrage that has created an environment for rent-seeking behaviour. The study concludes that policy inconsistencies in implementing economic policies and reforms in Malawi have been instrumental in influencing the suboptimal growth patterns of the Malawian economy.
Keywords: Malawi; Macroeconomic Reforms; Economic Growth